Sharia-Based Financial Literacy and Digital Innovation in Strengthening MSME Business Performance - Ginna Novarianti Dwi Putri Pramesti; Agus Rohmat Hidayat (Politeknik Siber Cerdika Internasional, 2026)
Sharia-based financial literacy and digital innovation are increasingly recognised as pivotal yet under-studied co-determinants of MSME business performance in Muslim-majority emerging economies. This study examines the individual and interactive effects of sharia-based financial literacy and digital innovation on MSME business performance in Indonesia. A quantitative approach with moderated multiple regression analysis was applied to primary data from 248 Muslim-owned MSMEs across West Java, Central Java, and East Java, selected through stratified random sampling. Variables were operationalized across nine dimensions and 27 indicators on a five-point Likert scale. Sharia-based financial literacy (B = 0.421, p < 0.001) and digital innovation (B = 0.318, p < 0.001) each significantly and positively affect MSME business performance. Their interaction is significant (B= 0.171, p = 0.002), indicating a synergistic effect with a Cohen's f² = 0.090 (small-to-medium). The integrated model accounts for 63.4% of variance in business performance. MSMEs that simultaneously develop Islamic financial literacy and embrace digital innovation achieve disproportionately higher business performance. Sharia financial institutions, digital ecosystem architects, and policymakers should design integrated halal-digital capacity programs targeting this synergistic pathway.